Examining the gender, ethnicity, and age dimensions of the healthy immigrant effect: Factors in the development of equitable health policy - Kobayashi Karen M; Prus Steven G (BMC, 2012)
Abstract This study expands on previous research on the healthy immigrant effect (HIE) in Canada by considering the effects of both immigrant and visible minority status on self-rated health for males and females in mid-(45-64) and later life (65+). The findings reveal a strong HIE among new immigrant middle-aged men, particularly non-Whites. For older men of color the reality is strikingly different: they are disadvantaged in health compared to their Canadian-born counterparts, even when a number of demographic, economic, and lifestyle factors are controlled. Health outcomes for immigrant women are in contrast to that of immigrant men. Among middle-aged women, immigrants, regardless of their ethnicity or number of years since immigration, are much more likely to report poor health compared to the Canadian-born. And, for older women, recent non-white immigrants are more likely to report better health compared to Canadian-born women, although this finding is explained by differences in demographic, economic, and lifestyle factors. Overall, the findings demonstrate the importance of considering the intersections of age, gender, and ethnicity for policymakers in assessing the health of immigrants.